JISMONIY MASHQLARNING INSON TANASIGA TA’SIRI - Hayitov, Jumaqul Negmatovich (Educational Research in Universal Sciences, 2023)
This article describes the effects of exercise on the human body. Everyone will always be healthy if they can use physical exercises wisely and correctly. This article, covered by us, explains in detail about physical exercises.